Patient-Reported Outcome Measures in Atopic Dermatitis and Chronic Urticaria are Underused in Clinical Practice - Cherrez-Ojeda, Ivan; Bousquet, Jean; Giménez-Arnau, Ana; Godse, Kiran; Krasowska, Dorota; Bartosińska, Joanna; Szczepanik-Kułak, Paulina; Wawrzycki, Bartłomiej; Kolkhir, Pavel; Allenova, Anastasiia; Allenov, Andrey; Tkachenko, Sergey; et al. (Elsevier BV, 2024)
Patient-reported outcome measures (PROMs) are validated and standardized tools that complement physician evaluations and guide treatment decisions. PROMs are crucial for monitoring atopic dermatitis (AD) and chronic urticaria (CU) in clinical practice, but there are unmet needs and knowledge gaps regarding their use in clinical practice.
Keywords: allergy; atopic dermatitis; chronic urticaria; dermatology; patient reported outcome measures